Thermodynamic origin of solute-enriched stacking-fault in dilute Mg-Zn-Y alloys. (March 2020) - Egami, M.; Ohnuma, I.; Enoki, M.; Ohtani, H.; Abe, E.
Abstract: We have investigated thermodynamic behaviors of dilute Mg-Zn-Y ternary alloys to form a unique solute-enriched stacking-fault (SESF), which is an intrinsic-II type stacking-fault ( I 2 -SF) enriched by the Zn and Y atoms and represents the structural-unit of the long-period stacking/order (LPSO) phase. SESF in the hexagonal-close-packed ( hcp ) Mg matrix forms a local face-centered-cubic ( fcc ) environment, and hence our thermodynamic analysis is based on the Gibbs energy comparison between hcp and fcc phases over the Mg-Zn-Y ternary composition ranges, using the calculation of phase diagrams (CALPHAD) method aided by the first principles calculations. We find that the Zn/Y co-segregations at the SESF provide a remarkable condition that the fcc layers become more stable than the hcp -Mg matrix. Furthermore, within the SESF, the following spinodal-like decomposition into the Mg-rich solid-solution and the Zn/Y-rich L 12 -type order phase causes a significant reduction of the total Gibbs energy of the system. These spontaneous thermodynamic behaviors explain why the fault layers can be remarkably stabilized in the LPSO-forming ternary Mg alloys, and also support a phenomenological origin of the Zn-Y clustering with the L 12 -type short-range order, which is known to occur for the LPSO phases and has been confirmed for the present SESF by electron microscopy experiments. Graphical abstract: Unlabelled Image Highlights: Thermodynamic insights how the solute-enriched stacking faults (SESFs) are stabilized in the LPSO-forming Mg-Zn-Y alloy. Zn/Y co-segregations at the SESFs realize the condition that the  fcc  layers become more stable than the  hcp -Mg matrix. Spontaneous spinodal-like decompositions within the SESFs lead to solute clustering to form robust Zn-Y clusters.